Prevalence of Trachoma in the North Region of Cameroon: Results of a Survey in 15 Health Districts - Noa Noatina, Blaise (Public Library of Science, 2014)
BACKGROUND: To estimate the prevalence of trachoma in the North Region of Cameroon in order to facilitate the planning of trachoma control activities in this region, a survey was carried out in 2011 and 2012 in 15 health districts (HDs). METHODOLOGY: A cross-sectional, two-stage cluster random sampling survey was carried out. The survey focused on two target populations: children aged 1 to 9 years for the prevalence of Trachomatous Inflammation-Follicular (TF) and those aged 15 and over for the prevalence of Trachomatous Trichiasis (TT). The sample frame was an exhaustive list of villages and neighborhoods of HDs. The World Health Organization simplified trachoma grading system was used for the recognition and registration of cases of trachoma. PRINCIPAL FINDINGS: 30,562 children aged 1 to 9 years and 24,864 people aged 15 and above were examined. In children aged 1–9 years, the overall prevalence of TF was 4.2% (95% confidence intervals (CI): 4.0–4.5%). Three (3) of 15 HDs in the region showed TF prevalence of ≥10% (Poli, Rey Bouba, and Tcholliré). The overall TT prevalence was 0.25% (95% CI: 0.20–0.33%). There were estimated 1265 TT cases in the region. The prevalence of blindness was 0.01% (95% CI: 0.00–0.03%), low vision was 0.11% (95% CI: 0.07–0.17%), and corneal opacity was 0.22% (95% CI: 0.17–0.29%). CONCLUSIONS/SIGNIFICANCE: This survey provides baseline data for the planning of activities to control trachoma in the region. The overall prevalence of TF in the region is 4.2%, and that of TT is 0.2%; three HDs have a TF prevalence ≥10%. These three HDs are eligible for mass drug administration with azythromycin, along with the implementation of the “F” and “E” components of the SAFE strategy.